Wicked fox - Cho, Kat. (2019)
After eighteen-year-old Gu Miyoung, a nine-tailed fox surviving in modern-day Seoul by eating the souls of evil men, kills a murderous goblin to save Jihoon, she is forced to choose between her immortal life and his.
Keywords: Murder -- Fiction; Soul -- Fiction; Animals, Mythical -- Fiction; Seoul (Korea) -- Fiction; Korea -- Fiction; Electronic books; Electronic books